Penggunaan Deteksi Gerak untuk Pengurangan Ukuran Data Rekaman Video Kamera CCTV - Jockie P Sagala; Ika Candradewi; Agus Harjoko (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2020)
Some cases the recording data of Closed Circuit Television (CCTV) is stored for future use. In the long term usage, the files size will grow larger and requiring large storage devices. In some cases, the recorded data not only image with the desired object but also the background images that may be recorded for long periods of time. This cases make data storage device usage to be less effective. So this research will design a system of CCTV devices that capable to select images to reduce the size of stored images data by image processing.The images selection of this system is based on based on adaptive median algorithm. When any object get detected, the images data to be saved is current input frame. Otherwise, the data to be saved is background model image. Background model on this system is adapted with the change visual data of background image.The results obtained from this research in the form of a CCTV system that are able to select recording data to be stored with image processing. The background model will be kept adapting with background visual data changes.